Challenges and strategies for incorporating sustainability into social oversight within certain Municipal School Feeding Councils in Minas Gerais under the National School Feeding Program - Nogueira, Ana Carolina Ratti; Sant'Anna, Monique de Oliveira; Garcia, Jaciara Reis Nogueira; Sanches, Lucas Daniel; Martins Dala Paula, Bruno (Geografares, 2024)
The study aimed to understand the role of certain Municipal School Food Councils (CAEs) in Minas Gerais in promoting sustainability within the National School Feeding Program (PNAE) and to evaluate the impact of virtual training, using action research as proposed by Thiollent. The CAEs are composed of representatives from civil society; education workers and students; parents of students; and representatives from the executive branch. During two sessions of a virtual workshop, discussion groups were conducted, with the conversations recorded, transcribed, and subjected to thematic content analysis as proposed by Bardin. School gardens and partnerships with technical assistance institutions were cited as opportunities to promote sustainability in the PNAE. Lack of support and knowledge about food and nutrition among the school community were highlighted as challenges. All CAEs reported their intention to include sustainability in the social oversight of the PNAE in their municipalities.